Priorities for research to take forward the health equity policy agenda (The World Health Organization, 2005)
Despite impressive improvements in aggregate indicators of health globally over the past few decades, health inequities between and within countries have persisted, and in many regions and countries are widening. Our recommendations regarding research priorities for health equity are based on an assessment of what information is required to gain an understanding of how to make substantial reductions in health inequities. We recommend that highest priority be given to research in five general areas: (1) global factors and processes that affect health equity and/or constrain what countries can do to address health inequities within their own borders; (2) societal and political structures and relationships that differentially affect people's chances of being healthy within a given society; (3) interrelationships between factors at the individual level and within the social context that increase or decrease the likelihood of achieving and maintaining good health; (4) characteristics of the health care system that influence health equity and (5) effective policy interventions to reduce health inequity in the first four areas.